Aplicaciones de la fibra acrílica de alta tenacidad en productos cementicios - Carbajal Romero, Enrique Luis (2021)
The present study is based on the possibility of locally producing high tenacity acrylic microfiber for the construction sector, so that the polypropylene reinforcement microfiber, which is imported and used in this sector, can be replaced. On the other hand, it is also sought to reduce, in the production of fibercement, the consumption of chrysotile mineral fiber (asbesto or amianto), which is harmful to health due to the generation of asbestosis in the respiratory system of human beings. Studies carried out on acrylic microfiber and fiber reinforced cement compounds show that it can be used in this field without undermining the mechanical properties of the final product, such as: concrete slabs, formwork, concrete segments, ductility walls limited, flat and corrugated fiber cement sheets. In Chapter I, we briefly describe Sudamericana de Fibras S.A. and we focus the problem to be solved, both for the production of fibercement as well as for concrete. In Chapter II, we describe the objectives of the investigation: a general objective and three specific objectives. In Chapters III and IV, we develop the scope of the investigation as well as the justification for the development of the research project. In Chapter V, we obtain the results for the industrial tests and tests performed. This chapter culminates with some improvements made to reduce production costs. Finally, this document is closed with the conclusions and recommendations for this research work.